E EFEKTIVITAS PENDIDIKAN KESEHATAN METODE AUDIO VISUAL AIDS (AVA) DENGAN METODE DISKUSI TERHADAP PENGETAHUAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DI SMK BINA BANUA BANJARMASIN - Ruslinawati Ruslinawati; Darmayanti Wulandatika (Journal of Nursing Invention, 2020)
Background: Breast self-examination (SADARI) is an effort to find out the normal condition of the breast that can be done by yourself as an early detection effort to find out any changes in the breast quickly. But unfortunately, many women do not know what SADARI is. Where increasing knowledge can be done by conducting health education where methods that can be used in conducting health education include lecture methods, group discussions, brainstorming, panels, role playing, demonstrations. Objective: to determine the Effectiveness of Health Education Video Media Discussion MethodMethods: This study used group discussion methods with video media and discussion methods on knowledge about SADARI at Bina Banua Banjarmasin Vocational School. Quasi-experimental quantitative research type with Equivalent Control Group Pre Test-Post Test Design with a population of 359 female students using proportional sampling technique with 42 respondents using a questionnaire of 18 statements. The test used paired t test and independent t test. Results: The results of the analysis before and after the intervention group P Value = 0.000 and before and after the control group P Value = 0.000. The results of data analysis of the level of knowledge after health education in two groups obtained a value of P Value = 0.000. Conclusion: there is a difference in the level of knowledge in each group.